2016
DOI: 10.1007/s11751-016-0247-5
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome of knee arthrodesis with a monorail external fixator

Abstract: Several methods for obtaining knee arthrodesis have been described in the literature and world; over, the commonest cause for arthrodesis is a failed arthroplasty. Less commonly, as in this series, post-infective or traumatic causes may also require a knee fusion wherein arthroplasty may not be indicated. We present salient advantages along with the radiological and functional outcome of twenty four patients treated with a single monorail external fixator. All patients went on develop fusion at an average of 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 9 publications
(10 reference statements)
0
4
0
Order By: Relevance
“…One common issue is leg length discrepancy post-surgery, a consequence of shortening the affected limb to enhance bone healing at the fusion site. Studies have reported limb shortening ranging from approximately 2.5 to 5.4 cm associated with knee arthrodesis procedures [6][7][8][9][10][11]. A second concern is the frequent insu ciency of autologous bone available for patients undergoing this procedure [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…One common issue is leg length discrepancy post-surgery, a consequence of shortening the affected limb to enhance bone healing at the fusion site. Studies have reported limb shortening ranging from approximately 2.5 to 5.4 cm associated with knee arthrodesis procedures [6][7][8][9][10][11]. A second concern is the frequent insu ciency of autologous bone available for patients undergoing this procedure [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…EFs have been used in several other treatment domains such as in reconstructive orthopaedics and fracture care. EFs are used for arthrodesis [ 68 ], treatment of failing or failed femoral plating [ 69 ], infected non-union fracture (femoral shaft) [ 70 ], treatment of bone loss [ 71 , 72 ], deformity correction [ 73 – 75 ] and treatment of osteomyelitis [ 76 ].…”
Section: Introductionmentioning
confidence: 99%
“…A study was conducted among patients with severe and recurrent congenital talipes equinovarus deformities, it showed that complete correction was obtained using (Ilizarov) EFs and had relatively few complications [ 79 ]. An EF is a safe and economically feasible procedure for reconstructive surgery of Charcot feet, and it improves activity level, minimises complications, and reduces secondary amputation [ 68 , 75 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ironically, clinical interest in knee arthrodesis procedures and outcomes remains constant, and there are a large number of published case reports and review articles (Somayaji et al 2008 ) on the subject. Some of these reports have focused on the conflicting methods of achieving fusion, including external fixation (Ravi and Chaikof 2010 ; Spina et al 2010 ; Roy et al 2016 ) and internal fixation by means of intramedullary nails (Leroux et al 2013 ; Lee et al 2012 ; Razii et al 2016 ) or dynamic compression plates (Roy et al 2016 ; Lv et al 2012 ). Clinical evidence indicates that internal fixation tends to be a simpler procedure; however, external fixation can be indicated in cases of substantial bone or tissue loss (Lee et al 2012 ).…”
Section: Introductionmentioning
confidence: 99%